in Others
189 views
0 votes
0 votes

??????????

in Others
189 views

2 Answers

1 vote
1 vote

Assume the base of the number is $x$.


Therefore,
$=> (4)x+(2)x=(11)x$
$=> 4x^0+2x^0=1x^1+1x^0$
$=> 4+2=x+1$
$=> 6=x+1$
$=> x=6-1$
$=>x=5$


Hence base should be 5 for the given expression.

 

edited by
0 votes
0 votes

Let the base be x

= $(4)_{x} + (2)_{x} = (11)_{x}$

= $4 + 2 = x + 1$

= $x = 6-1 = 5$

Correct answer: 5

Related questions

1 vote
1 vote
1 answer
1
0 votes
0 votes
1 answer
2
0 votes
0 votes
1 answer
3
0 votes
0 votes
1 answer
4
Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true